Alcohol Fuels Current Technologies and Future Prospect - Yun, Yongseung (IntechOpen, 2020)
Alcohol fuels must remain as an essential component for the realization of a sustainable low-carbon society. Use of locally available, under-utilized feedstock becomes important for local energy security as well as an option for distributed energy infrastructure. Utilizing the available feedstock that has not been properly regarded as a legitimate resource due to economic and social reasons should be the focal point in the search for possible resources for alcohol fuels. Lignocellulosic biomass and algal species are feedstocks that suit the purpose. This book can provide a brief introduction regarding the recent advances in the alcohol fuel field that is in constant challenge from recent issues on CO2, shale oil, power-to-gas, and hydrogen.